HUBUNGAN INTENSITAS NYERI PUNGGUNG BAWAH UNILATERAL DENGAN DERAJAT OSTEOARTRITIS LUTUT KONTRALATERA - Edy Irwanto; Dwi Pudjonarko; Hermina Sukmaningtyas (PERDOSNI, 2019)
THE CORRELATION OF UNILATERAL LOW BACK PAIN INTENSITY AND THE DEGREE OF CONTRALATERAL KNEE OSTEOARTHRITISABSTRACTIntroduction: Low back pain (LBP) is one of the most common and recurring forms of musculoskeletal pain. In back injuries or disc degenerative diseases that cause chronic LBP will increase the burden on the knee joint, thereby triggering or exacerbating the occurrence of osteoarthritis (OA) of the knee.Aims: To analyze the correlation of unilateral LBP intensity and the degree of contralateral knee OA.Methods: Cross-sectional observational analytic study of LBP patients who went to the neurology polyclinic of RSUP Dr. Kariadi, Semarang, from November 2018 to March 2019. The diagnosis of knee OA was made clinically based on the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) questionnaire and radiological with Kellgren-Lawrence scores. Fisher’s exact test was used to see the correlation between variables, and the results of the bi- variate analysis was continued with a logistic regression multivariate test to find out the variables that influence the degree of knee OA.Results: There were 36 subjects, the majority of which were women (58.3%) with an average age of 53.88±11.01 years. A significant relationship was found between the unilateral LBP intensity (p=0.004; Odds ratio/OR=32,500) and malalignment of the knee joint (p=0.024; OR=11.67) with the degree of contralateral knee OA based on the WOMAC score.Discussion: The unilateral LBP intensity and malalignment of the knee joint can increase the risk of contralateral knee OA based on WOMAC scores of 32.5 and 11.7 times, respectively.Keywords: Kellgren-Lawrence score, low back pain, osteoarthritis of the knee, WOMAC scoreABSTRAKPendahuluan: Nyeri punggung bawah (NPB) adalah salah satu bentuk nyeri muskuloskeletal yang paling umum terjadi dan dapat berulang. Pada cedera punggung atau penyakit degeneratif diskus yang menyebabkan NBP kronik akan meningkatkan beban pada sendi lutut, sehingga memicu atau memperparah terjadinya osteoartritis (OA) lutut.Tujuan: Untuk mengetahui hubungan intensitas NPB unilateral dengan derajat OA lutut kontralateral.Metode: Penelitian analitik observasional secara potong lintang terhadap pasien NPB yang berobat ke Poliklinik Saraf RSUP Dr. Kariadi, Semarang, pada bulan November 2018 hingga Maret 2019. Diagnosis OA lutut ditegakkan ber- dasarkan klinis menggunakan kuesioner Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) dan radiologis dengan skor Kellgren-Lawrence. Korelasi antar variabel menggunakan uji Fisher’s exact, hasil analisis bivariat dilanjutkan dengan uji multivariat regresi logistik untuk mengetahui variabel yang berpengaruh terhadap derajat OA lutut.Hasil: Didapatkan 36 subjek yang mayoritas perempuan (58,3%) dengan rerata usia 53,88±11,01 tahun. Didapatkan hubungan yang bermakna antara intensitas NPB unilateral (p=0,004; rasio Odds/RO=32,500) dan malalignment sendi lutut (p=0,024; RO=11,67) dengan derajat OA lutut kontralateral berdasarkan skor WOMAC.Diskusi: Intensitas NPB unilateral dan malalignment sendi lutut dapat meningkatkan risiko terjadinya OA lutut kontralateral berdasarkan skor WOMAC masing-masing sebanyak 32,5 dan 11,7 kali.Kata kunci: Nyeri punggung bawah, osteoartritis lutut, skor WOMAC, skor Kellgren-Lawrence